Adjustment of regional climate model output for modeling the climatic mass balance of all glaciers on Svalbard - Möller, Marco; Obleitner, Friedrich; Reijmer, Carleen H.; Pohjola, Veijo A.; Głowacki, Piotr; Kohler, Jack (RWTH Aachen University, 2016)
Journal of geophysical research : JGR / D 121(10), 5411-5429 (2016). doi:10.1002/2015JD024380 : Published by Wiley, Hoboken, NJ